KETERLIBATAN ORANG TUA DALAM KEGIATAN STUDY FROM HOME DI WILAYAH PERBATASAN PADA MASA PANDEMI - Winda Lidia Lumbantobing; Yeremia Niaga Atlantika (Universitas Bina Bangsa, 2021)
This article aims to describe the involvement of parents in supporting the learning activities of elementary school children during the Covid-19 pandemic in the West Kalimantan – Malaysia border area. The research method used was qualitative with a case study approach. Data was collected by interview using thematic analysis on 3 parents of students, 2 teachers and 3 elementary school students in border areas. The results of the study reveal that the involvement of parents in learning activities in border areas, namely; provide facilities for children to support study from home activities, become a source of children's learning and act as teacher intermediaries in distributing material to students and student intermediaries in submitting student assignments to teachers.